Organic particle and film
Patent Information
- Application Number
- JP2023139599
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-30
- Publication Date
- 2025-03-13
AI Technical Summary
【0007】 本発明の有機粒子は粒子径制御および塗工性に優れることから各種コーティング用の粒子として用いることができる。具体的には日用品·自動車·電子·電気部品用の接着成分や二次電池等の各種電池のシャットダウン剤として好適に用いることができる。 また本発明の有機粒子を有するフィルムは優れた電気特性と安全性を両立することから、水素電池、空気電池、燃料電池、リチウムイオン二次電池、コンデンサ、電気二重層キャパシタ、リチウムイオンキャパシタ等の各種蓄電デバイス、中でも、電池用、特にリチウムイオン二次電池用のセパレータ等に好適に用いることができる。
Smart Images

Figure 2025033693000001 
Figure 2025033693000002 
Figure 2025033693000003
Abstract
Description
[Technical field]
[0001] The present invention relates to organic particles that have excellent dispersion stability and allow control of particle size, and to a film that has a layer containing the organic particles and thereby achieves both excellent electrical properties and safety. [Background technology]
[0002] Organic particles mainly composed of polyolefins are used as adhesives, pressure sensitive adhesives, toners, pigments, and resin additives for coatings, taking advantage of their thermal properties and chemical and water resistance (Patent Documents 1-3). In particular, for coating applications, coating films in which organic particles are applied to the film surface, taking advantage of their thermal properties and fluidity, are being considered. In particular, coating films in which a coating film made of organic particles is formed on a porous substrate are widely used as separators for batteries, capacitors, etc., because they are excellent in mechanical properties in addition to electrical insulation and ion permeability. In recent years, secondary batteries have come to be used for various purposes such as automobiles and electronic devices, but there have been cases in which abnormalities occur in the battery during use, causing the battery to explode due to thermal runaway. In response to this, as a safety device for batteries, consideration has been given to imparting shutdown properties to the separator, which would cause parts of the separator to melt gradually at lower temperatures before the entire separator melts when the battery abnormally heats up, thereby blocking the pores in the separator and cutting off the current before the temperature reaches the range where thermal runaway begins.The use of organic particles made of olefins and coating films made of these particles as shutdown agents has been considered (Patent Documents 4 to 10). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent No. 1803328 [Patent Document 2] Patent No. 5656844 [Patent Document 3] JP 2012-041495 A [Patent Document 4] Japanese Patent Application Publication No. 9-219185 [Patent Document 5] International Publication No. 2018 / 017944 [Patent Document 6] International Publication No. 2010 / 008003 [Patent Document 7] JP 2009-114434 A [Patent Document 8] Patent No. 5778657 [Patent Document 9] JP 2007-269826 A [Patent Document 10] Japanese Patent Application Publication No. 1-45448 Summary of the Invention [Problem to be solved by the invention]
[0004] However, these techniques do not allow for particle size control unless a low-viscosity resin is used, making it difficult to obtain stable organic particles. In addition, when the amount of functional groups is increased by copolymerization to stably disperse the organic particles in the solvent, the dispersion stability can be maintained, but the thermal properties are significantly reduced, and the shutdown function may be activated (the shutdown function may malfunction) below 80°C, which is the normal operating temperature range of the battery, making it difficult to control the temperature at which the shutdown function begins.
[0005] The object of the present invention is to solve the above-mentioned problems by providing organic particles that have excellent dispersion stability and allow control of particle size, and a film that has a layer containing the organic particles and thereby exhibits a shutdown property that achieves both excellent electrical properties and safety. [Means for solving the problem]
[0006] The organic particles and film of the present invention have the following characteristics to solve the above problems. [I] The main component is polyolefin, and in the FT-IR spectrum, -1 More than 1500cm -1Maximum absorption peak intensity (S1) in the range of 1700 cm -1 More than 1800cm -1 Organic particles having a ratio (S1 / S2) of 2 to the maximum absorption peak intensity (S2) in the following range: [II] Complex viscosity at 120°C is 1.0×10 2 Pa·s or more 5.0×10 3 The organic particle according to [I], wherein the viscosity is 0.01 Pa·s or less. [III] In the FT-IR spectrum, 1400 cm -1 More than 1500cm -1 Maximum absorption peak intensity (S1) in the range of 1700 cm -1 More than 1800cm -1 The organic particles according to [I] or [II], wherein the ratio (S1 / S2) to the maximum absorption peak intensity (S2) in the following range is 5 or more and 75 or less. [IV] The organic particles according to any one of [I] to [III], having a D50 of 0.05 μm or more and 1.5 μm or less. [V] The organic particles according to any one of [I] to [IV], having a D90 of 2.0 μm or less. [VI] The organic particles according to any one of [I] to [V], having a D10 of 0.02 μm or more. [VII] A dispersion in which the organic particles according to any one of [I] to [VI] are dispersed in water and / or an organic solvent. [VIII] A film comprising the organic particles according to any one of [I] to [VI]. [IX] An electricity storage device comprising the organic particles according to any one of [I] to [VI]. [X] A film having a layer (I) containing organic particles on at least one surface of a porous substrate, the organic particles being mainly composed of polyolefin, and having a wavelength of 1400 cm in the FT-IR spectrum. -1 More than 1500cm -1 Maximum absorption peak intensity (S1) in the range of 1700 cm -1 More than 1800cm -1 A film having a ratio (S1 / S2) of 2 or more to the maximum absorption peak intensity (S2) in the following range, and 100 or less. [XI] The complex viscosity of the organic particles at 120° C. is 1.0×10 2 Pa·s or more 5.0×10 3 The film according to [X], wherein the Pa·s is or less. [XII] In the FT-IR spectrum of the organic particles, -1 More than 1500cm -1 Maximum absorption peak intensity (S1) in the range of 1700 cm -1 More than 1800cm -1 The film according to [X] or [XI], wherein the ratio (S1 / S2) to the maximum absorption peak intensity (S2) in the following range is 5 or more and 75 or less. [XIII] The film according to any one of [X] to [XII], wherein the layer (I) contains inorganic particles. [XIV] The film according to any one of [X] to [XIII], wherein the porous substrate is mainly composed of polyolefin. [XV] The film according to any one of [X] to [XIV], which has a 10 μm converted puncture strength of 5.0 N / μm or more. [XVI] The film according to any one of [X] to [XV], which has a layer (II) having a composition different from that of layer (I) on the other side of the porous substrate. [XVII] An electricity storage device having a positive electrode, the film according to [XVI], and a negative electrode, wherein the layer (I) of the film is disposed toward the negative electrode side and the layer (II) is disposed toward the positive electrode side. [XVIII] [VIII] or [X] includes a film according to the present invention. Effect of the Invention
[0007] The organic particles of the present invention have excellent particle size controllability and coatability, and can be used as particles for various coatings. Specifically, they can be suitably used as adhesive components for daily necessities, automobiles, electronic and electrical parts, and as shutdown agents for various batteries such as secondary batteries. Furthermore, since the film having the organic particles of the present invention has both excellent electrical properties and safety, it can be suitably used for various electricity storage devices such as hydrogen batteries, air batteries, fuel cells, lithium ion secondary batteries, capacitors, electric double layer capacitors, and lithium ion capacitors, among which, it can be suitably used as a separator for batteries, particularly for lithium ion secondary batteries. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] The organic particles of the present invention are mainly composed of polyolefin. Here, "mainly composed" refers to a component that accounts for 80% by mass or more of the components constituting the organic particles. Examples of polyolefins used in the organic particles include α-olefins such as ethylene, propylene, 1-butene, 3-methyl-1-butene, 4-methyl-1-pentene, 3-methyl-1-pentene, 1-heptene, 1-hexene, 1-octene, 1-decene, and 1-dodecene, conjugated or non-conjugated dienes such as butadiene, ethylidene norbornene, dicyclopentadiene, and 1,5-hexadiene, and polymers obtained by polymerizing monomers such as styrene, vinyl acetate, and vinyl alcohol alone or in combination of two or more kinds. Specific examples include homopolymers such as polyethylene, polypropylene, and polybutene, and copolymerized olefins such as ethylene-propylene copolymers, ethylene-vinyl acetate copolymers, ethylene-ethyl acrylate copolymers, ethylene-vinyl alcohol copolymers, and ethylene-styrene copolymers, but are not limited thereto.
[0009] When copolymerized polyethylene is used for the organic particles of the present invention, the copolymerization component ratio of monomers other than ethylene is from 1.0 mol% to 30.0 mol%, assuming that the total monomer components constituting the polymer are 100 mol%, which is preferable from the viewpoints of maintaining the crystalline properties of the resin, promoting the softening of the organic particles by controlling the amorphous fluidity at low temperatures, and imparting an appropriate degree of amorphousness to the resin during the production of the organic particles, thereby enabling the production of particles with a uniform particle size.
[0010] The polyolefin used in the organic particles of the present invention preferably has a weight average molecular weight of 50,000 or more and 300,000 or less from the viewpoint of producing the organic particles, and more preferably 50,000 or more and 200,000 or less from the viewpoint of maintaining the initial properties.
[0011] The organic particles of the present invention preferably use a resin composition in which an olefin wax is mixed with a polyolefin. Here, the olefin wax refers to a polyolefin having a weight-average molecular weight of 30,000 or less. By blending this olefin wax, it becomes possible to control the flow characteristics of the polyolefin resin, and the complex viscosity described below can be achieved. Specific examples of the olefin wax that can be used in the present invention include polyethylene-based resins such as low-density polyethylene, linear polyethylene (ethylene-α-olefin copolymer), and high-density polyethylene, polypropylene-based resins such as polypropylene and ethylene-propylene copolymer, and waxes of poly(4-methylpentene-1), poly(butene-1), and ethylene-vinyl acetate copolymer. The weight-average molecular weight of the polyolefin resin and the olefin wax can be evaluated by GPC (gel permeation chromatography) measurement.
[0012] When a resin obtained by mixing a polyolefin resin with an olefin wax is used for the organic particles of the present invention, the concentration of the olefin wax is preferably 5% by mass or more and 40% by mass or less, and more preferably 10% by mass or more and 30% by mass or less, from the viewpoint of both controlling the resin properties of the composition and dispersibility, when the mixed resin composition is taken as 100% by mass. If the concentration of the olefin wax exceeds 40% by mass, the fluidity of the polyolefin resin becomes too high, so that when the organic particles are applied to a substrate film, the properties may be deteriorated due to the progress of plasticization or the decrease in viscosity during melting. If the concentration of the olefin wax is less than 5% by mass, the effect of blending the olefin wax may be weakened, and the dispersibility may be reduced, or the fluidity of the polyolefin resin, which is the main component, may not be controlled. The blending amount of the olefin wax can be confirmed by a molecular weight distribution curve obtained by GPC measurement or quantitative analysis by IR.
[0013] The olefin wax used in the organic particles of the present invention preferably has an acid value, as measured in accordance with JIS K0070 (1992), of 5 mgKOH / g or more and 200 mgKOH / g or less from the viewpoint of maintaining dispersibility during the production of the organic particles, and preferably has an acid value, as measured in accordance with JIS K0070 (1992), of 30 mgKOH / g or more and 200 mgKOH / g or less from the viewpoint of maintaining the durability of the olefin wax and the amount of functional groups contained therein.
[0014] The organic particles of the present invention have a wavelength of 1700 cm in FT-IR spectroscopy. -1 More than 1800cm -1 It has an absorption peak in the following range. The peak confirmed in this region indicates that the resin constituting the organic particles has functional groups derived from CO bonds. By having a peak in this region, the affinity for water is improved when dispersing the organic particles in water, and it is possible to prevent aggregation and form a particle dispersion with a fine and uniform average particle size.
[0015] The organic particles of the present invention have a wavelength of 1400 cm in FT-IR spectroscopy. -1 More than 1500cm -1 Maximum absorption peak intensity (S1) in the range of 1700 cm -1 More than 1800cm -1 The ratio (S1 / S2) to the maximum absorption peak intensity (S2) in the range below is 2 to 100. 1400cm -1 More than 1500cm -1 In the following region, peaks derived from the C-H bonds of the olefin resin that constitutes the organic particles can be observed. The maximum absorption peak intensity (S1) of the peak observed in this region is used as the reference band, and the peak at 1700 cm -1 More than 1800cm -1The relative value of the amount of functional groups contained in the organic particles can be estimated by calculating the ratio of (S1 / S2) from the maximum absorption peak intensity (S2) of the peak observed in the following range. When the maximum absorption peak intensity ratio (S1 / S2) is smaller than 2, the organic particles contain many functional groups, and therefore the organic particles are composed of an olefin wax having functional groups alone or a composition mainly composed of the same, or a resin copolymerized with a monomer having functional groups alone or a composition mainly composed of the same. This may result in a decrease in initial properties when the organic particles are made into organic particles, or a decrease in properties when the organic particles are used in practice. When the maximum absorption peak intensity ratio (S1 / S2) is larger than 100, the organic particles contain too few functional groups, and therefore the hydrophilicity required for water dispersion cannot be expressed, and when the organic particles are made into organic particles, the particle size may not be controlled or the dispersion stability may decrease. The maximum absorption peak intensity ratio (S1 / S2) is preferably in the range of 2 to 75, more preferably 3 to 50, and even more preferably 5 to 30. The IR spectrum waveform and maximum absorption peak intensity ratio of the organic particles can be controlled by using the above-mentioned composition. The IR spectrum and maximum absorption peak intensity ratio (S1 / S2) of the organic particles can be evaluated by the method described below.
[0016] The method for mixing the olefin wax with the olefin resin may be, but is not limited to, mixing in advance by a melt kneading method or blending during the production process of the organic particles.
[0017] The organic particles of the present invention preferably have a softening start temperature of 80°C or more and 120°C or less. The softening start temperature refers to the temperature at which the resin constituting the organic particles begins to substantially deform when heated. By having the above-mentioned softening start temperature, it is possible to suppress deformation of the organic particles at low temperatures and to cause the particles to exhibit fluidity in a temperature range where the particles are highly processable. If the softening start temperature is lower than 80°C, the organic particles may exhibit adhesion at room temperature, resulting in a decrease in handleability, or when the organic particles are arranged on the surface of a film by coating, the organic particles may soften at low temperatures, causing a decrease in properties. If the softening start temperature is higher than 120°C, the organic particles may have a high flow point, resulting in a decrease in processability and handleability, or when the organic particles are arranged on the surface of a film by coating, the difference in softening temperature between the particles and the substrate may be small, making it difficult to exhibit the properties due to the organic particle coating. The softening start temperature is preferably 80°C or more and 110°C or less, more preferably 90°C or more and 110°C or less. The softening temperature can be achieved by selecting the resin described above. The softening starting temperature can be confirmed by the method described later.
[0018] From the viewpoint of controlling the softening temperature, the organic particles of the present invention have a complex viscosity of 1.0×10 at 80° C. 4 The complex viscosity at 80°C is preferably higher than 1.0×10. 8 It is less than Pa·s.
[0019] The organic particles of the present invention have a complex viscosity of 1.0×10 at 120° C. 2 Pa·s or more 5.0×10 3 It is preferable that the viscosity is less than 4.0×10 Pa s. 2 Pa·s or more 5.0×10 3It is more preferable that the complex viscosity is 1.0×10 or less. By having the above complex viscosity, when the organic particles are used as a shutdown agent for a battery, excellent shutdown properties can be exhibited when the battery abnormally heats up. Furthermore, when the organic particles are used as a component of an adhesive or the like, excellent transferability to the surface of the adherend can be exhibited, thereby exhibiting an anchor effect. The complex viscosity at 120°C is 1.0×10 2 If the viscosity is less than Pa·s, the resin viscosity is too low and when a porous substrate is used, as described below, it may be adsorbed and not form a layer, or when used as an adhesive component, it may cause a decrease in adhesive strength. 3 If it exceeds Pa·s, the viscosity is too high and the resin may not flow even when melted, making it impossible to form a film necessary for the shutdown property to be expressed, or the transferability may decrease and adhesiveness may be difficult to be expressed. The complex viscosity at 120°C can be set within the above range by using the resin and resin composition described above. The complex viscosity at 120°C can be evaluated using the method described below.
[0020] The organic particles of the present invention preferably have a particle diameter (D50: median diameter) of 50% value corresponding to the median of particle size distribution (cumulative distribution) obtained by laser diffraction method (a method of determining particle diameter by analyzing the intensity distribution of diffracted light obtained by irradiating particles with a laser beam) of 0.05 μm to 1.5 μm, more preferably 0.1 μm to 1.0 μm. By using organic particles with the above D50, a uniform and high-density layer can be formed when the organic particles are coated on the film surface, and excellent properties can be expressed. If D50 exceeds 1.5 μm, the particle diameter becomes large relative to the thickness of the layer to be formed by coating during thin film coating, so that the coatability may decrease or the particles may easily fall off. If D50 is less than 0.05 μm, the particle diameter becomes too small, so that when coated on a film, the density of the coating film may become too high, and the properties as a coating film may decrease.
[0021] The organic particles of the present invention preferably have a particle size (D10) of 10% of the cumulative distribution obtained by particle size distribution measurement of 0.02 μm or more, more preferably 0.05 μm or more. By setting D10 in the above range, it is possible to prevent fine particles from remaining and to make the particle size uniform. If D10 exceeds 0.02 μm, the ratio of particles smaller than the above-mentioned D50 increases, which may cause deterioration or variation in the film properties. The upper limit of D10 is preferably as close to D50 as possible from the viewpoint of making the particle size uniform.
[0022] The organic particles of the present invention preferably have a particle size (D90) of 2.0 μm or less, more preferably 1.5 μm or less, of the 90% value of the cumulative distribution obtained by particle size distribution measurement. When D90 satisfies the above range, the width of the particle size distribution can be narrowed, and a uniform coating film can be formed when coated on a film. If D90 is larger than 2.0 μm, the ratio of large particles to the thickness of the layer to be formed by coating during thin film coating becomes large, so that the coatability may decrease or the condition of the coating film may deteriorate. From the viewpoint of uniformity of the particle size, the lower limit of D90 is preferably as close to D50 as possible. The particle size can be achieved by applying the manufacturing method described later. The particle size can also be evaluated by the method described later.
[0023] The organic particles of the present invention can also be dispersed in a solvent to form a dispersion. Examples of the solvent used to disperse the organic particles include water, alcohols, ketones, DMSO, and DMF. Examples of the alcohol include methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, and 2-butapanol. The solvent used in the dispersion may be used alone, or two or more types of solvents may be mixed and used as desired. Among the above organic solvents, when considering the impact on the environment, it is preferable to use water as the main component of the solvent. Here, the main component of the solvent of the dispersion refers to a component that is contained in an amount of 80% by mass or more when the entire solvent of the dispersion is taken as 100% by mass.
[0024] When organic particles are used as a dispersion, the dispersion may contain thickeners, preservatives, dispersants, pH adjusters, etc., to the extent that the properties of the organic particles are not impaired. In addition, inorganic particles and other organic particles may also be blended.
[0025] Methods for making organic particles into a dispersion include, but are not limited to, a method in which, when a solvent is used in the process of producing the organic particles, the solvent is replaced with a solvent to be used when making the dispersion, and a method in which a powder of the organic particles is mixed with a solvent and dispersed in the solvent using a stirrer, a disperser, or the like.
[0026] One embodiment of the present invention includes coatings, adhesives and films containing the organic particles of the present invention.
[0027] The coating agent containing organic particles of the present invention refers to a liquid dispersion for applying organic particles to a general substrate and forming a layer containing organic particles on the surface. Examples of general substrates include metals such as iron, stainless steel, copper, aluminum, and brass, glass products such as glass plates and woven and nonwoven fabrics of glass fibers, polyolefins such as polyethylene and polypropylene, polyoxymethylene, polyimide, polyamideimide, polyester, polysulfone, polyethersulfone, polyetheretherketone, and liquid crystal polymers, resin films and sheets, injection and extrusion molded products and coatings, general-purpose rubbers such as SBR, butyl rubber, NBR, and EPDM, molded products and coatings such as silicone rubber and fluororubber, woven and nonwoven fabrics of natural and synthetic fibers, and laminated substrates formed by combining these, but are not limited thereto. These substrates may be surface-treated, such as roughened, antioxidized, and easily adhesive.
[0028] The composition of the dispersion of the coating agent containing the organic particles of the present invention may include, in addition to the organic particles of the present invention, solvents such as water and organic solvents, binders, inorganic particles, coloring pigments, stabilizers, thickeners, decomposition accelerators, rust inhibitors, preservatives, antifoaming agents, etc., within the range that does not impair the properties of the organic particles.
[0029] From the viewpoint of expressing the characteristics of the organic particles, the solids concentration of the organic particles contained in the coating agent containing the organic particles of the present invention is preferably 5 to 50 mass %, and more preferably 10 to 40 mass %, when the concentration of the entire coating agent is taken as 100 mass %.
[0030] The coating agent containing the organic particles of the present invention can be applied by a coating method used for ordinary coating materials, such as, but not limited to, spray coating, roll coating, coating with a doctor blade, dip (immersion) coating, impregnation coating, spin flow coating, curtain flow coating, coating with a bar coater, gravure coating, microgravure coating, etc.
[0031] Applications of the coating agent containing the organic particles of the present invention include, but are not limited to, electric and electronic parts, automobile parts, battery parts, daily necessities, packaging materials, construction / industrial materials, printing toners, coatings for various metal products, packaging materials, etc.
[0032] The adhesive containing organic particles of the present invention refers to the coating agent containing organic particles that can exhibit adhesiveness by melting organic particles.Examples of the uses of the adhesive include, but are not limited to, packaging material adhesive, paper adhesive, paper container coating agent, lid material adhesive, in-mold transfer foil adhesive, steel plate adhesive, solar cell module adhesive, flocking adhesive, power storage device adhesive, automotive component adhesive, heterogeneous substrate adhesive, etc.
[0033] Next, the film containing organic particles of the present invention will be described. The film containing organic particles of the present invention refers to a film-like material containing organic particles on one or both sides or in the film itself. Methods for incorporating organic particles into a film include, but are not limited to, a method of applying the coating agent described above to a film using the method described above, and a method of blending organic particles into the raw material for forming the film to form a film. Compositions constituting the film include, but are not limited to, polyolefins such as polyethylene and polypropylene, polyoxymethylene, polyimide, polyamideimide, polyester, polysulfone, polyethersulfone, polyetheretherketone, and liquid crystal polymers.
[0034] Applications of the film containing the organic particles of the present invention include, but are not limited to, electric and electronic parts, automobile parts, battery parts, daily necessities, packaging materials, and construction and industrial materials.
[0035] As one embodiment of the present invention, there is provided a film having a porous substrate and a layer (I) containing organic particles on at least one surface of the porous substrate, the organic particles being mainly composed of polyolefin, and having a peak at 1400 cm in the FT-IR spectrum. -1 More than 1500cm -1 Maximum absorption peak intensity (S1) in the range of 1700 cm -1 More than 1800cm -1 Examples of such films include those having a ratio (S1 / S2) of 2 to the maximum absorption peak intensity (S2) in the following range of 2 to 100. When the organic particles contained in layer (I) are localized in layers in the film at a high concentration, the film can exhibit a shutdown property in which the film melts with heat and electrically closes the pores contained in the film completely when the battery generates heat due to an abnormality when the film is used as a battery separator. By having this function, the film of the present invention can improve the safety of the battery during daily use.
[0036] The porous substrate used in the film of the present invention preferably has micropores inside and a structure (through holes) in which these micropores are connected from one surface to the other surface. Examples of the porous substrate include porous membranes, nonwoven fabrics, and porous membrane sheets made of fibrous materials. Among them, a microporous membrane mainly composed of polyolefin (hereinafter, referred to as a polyolefin microporous membrane) is preferable from the viewpoint of electrical insulation and durability against electrolytic solution. Here, the term "mainly composed of polyolefin" refers to a component that is contained in an amount of 80 mass% or more of the components constituting the material. The resin constituting the polyolefin microporous membrane can be a single polyolefin resin such as polyethylene, polypropylene, polybutene-1, poly4-methylpentene-1, or a mixture of these resins, or a resin obtained by randomly or block-copolymerizing the monomers constituting these resins. Among them, it is preferable to use polyethylene and / or polypropylene as the main component from the viewpoint of achieving both electrical properties and safety.
[0037] The method for forming the through holes in the polyolefin microporous membrane used in the porous substrate of the present invention may be either a wet method (a method in which the raw material resin and a solvent are melt-mixed and formed into a plate-like sheet / stretched, and then the solvent is washed / removed with a solvent to make the membrane porous) or a dry method (a method in which the resin is melted, extruded into a sheet, and then stretched to make the membrane porous).
[0038] The porous substrate used in the present invention may be unstretched or stretched in a uniaxial or biaxial direction, but is preferably stretched at least in a uniaxial direction from the viewpoint of improving the mechanical properties of the porous substrate. As a method for stretching the film at least in a uniaxial direction, it is preferable to stretch the film at a predetermined ratio after heating by a tenter method, a roll method, an inflation method, or a combination of these. In the case of biaxial stretching, any of simultaneous biaxial stretching, sequential stretching, and multi-stage stretching (for example, a combination of simultaneous biaxial stretching and sequential stretching) may be used.
[0039] When ultra-high molecular weight polyethylene is used as the raw material of the polyolefin porous membrane used in the porous substrate of the present invention, it is preferable to stretch (re-stretch) at least uniaxially at a temperature below the melting point of the resin after biaxial stretching. By having the above process, it is preferable from the viewpoint of suppressing the orientation relaxation of molecular chains, forming a thermally stable structure, improving the membrane strength and promoting low heat absorption.
[0040] The porous substrate used in the present invention may contain various additives such as antioxidants, heat stabilizers, antistatic agents, lubricants made of inorganic or organic particles, antiblocking agents, fillers, and incompatible polymers.
[0041] The porous substrate used in the film of the present invention may be either a single membrane or a laminated membrane having multiple layers.When the polyolefin porous membrane is a polyolefin microporous membrane having a laminated structure, its laminated structure may be, for example, a microporous membrane made of two different olefin compositions A and a microporous membrane made of olefin composition B, and may include, but is not limited to, two layers of A / B, three layers of A / B / A, B / A / B, A / B / A / B / A, B / A / B / A / B, etc. In addition, it may be a laminated structure in which a layer made of a different composition is added in addition to the olefin compositions A and B.
[0042] When a polyolefin microporous membrane having a laminated structure is used as the porous substrate for the film of the present invention, it is preferable that any of the layers in the layer structure contains a layer mainly composed of polypropylene, from the viewpoint of improving the heat resistance of the porous substrate and enhancing safety.
[0043] When the porous substrate used in the film of the present invention is mainly composed of polyethylene, the weight average molecular weight of the polyethylene is preferably 1.0×10 6 It is preferable that the value is 1.5×10 or more. 6 The upper limit of the weight average molecular weight is preferably 1.0×10 or more from the viewpoint of moldability. 7The following is preferable. By using polyethylene having the above molecular weight, the orientation relaxation of the film can be suppressed, the crystal structure can be maintained, and excellent heat resistance and film strength can be expressed, thereby improving the safety of the battery. By setting the weight average molecular weight to the above range or more, the relaxation time of the molecular chain orientation formed by stretching is shortened, and the deterioration of heat resistance and film strength due to the deterioration of the retention of the crystal structure at high temperatures can be suppressed. In addition, by setting the weight average molecular weight to the above range or less, the deterioration of moldability due to the increase in stretching torque can be suppressed.
[0044] The porous substrate used in the film of the present invention may be made of different materials, for example, a laminate of a porous membrane and a nonwoven fabric.
[0045] The thickness of the porous substrate used in the film of the present invention is preferably from 1 μm to 15 μm, and more preferably from 2 μm to 13 μm from the viewpoint of miniaturization of the battery.
[0046] The thickness of the layer (I) constituting the film of the present invention is preferably from 1 μm to 10 μm, and more preferably from 1 μm to 7 μm, from the viewpoint of miniaturization of the battery.
[0047] The thickness of the film of the present invention is preferably 2 to 25 μm in order to maintain the insulation distance and ensure safety when used as a separator, more preferably 3 to 23 μm, and even more preferably 3 to 20 μm. The thicknesses of the film, the porous substrate, and the layer (I) can be evaluated by the methods described below.
[0048] The organic particles contained in the layer (I) constituting the film of the present invention have a wavelength of 1700 cm in FT-IR spectroscopy. -1 More than 1800cm -1It has an absorption peak in the following range. This peak indicates that the resin constituting the organic particles has a hydrophilic functional group. By having this peak, the affinity to water is improved when the organic particles are dispersed in water, aggregation is prevented, and a particle dispersion having a fine and uniform average particle size can be obtained, and a uniform coating film can be formed when the layer (I) is applied to a porous substrate.
[0049] It is preferable that the layer (I) constituting the film of the present invention is such that when heated to 120°C or higher, the organic particles contained therein melt to form a film capable of blocking the passage of gases and ions. This property allows the film to exhibit excellent shutdown properties. When heated to 120°C, the shape of the organic particles may not be completely melted and flowed to maintain the particle shape, or may be partially melted and deformed to partially retain the particle shape.
[0050] The layer (I) constituting the film of the present invention may contain a resin component different from the organic particles as a binder in order to bind the organic particles to the surface of the porous substrate. Examples of binders include polyvinylidene fluoride (PVDF), acrylic, acrylic copolymers, fluorine-based rubber, styrene butadiene rubber (SBR), polyvinyl alcohol (PVA), polyvinyl butyral (PVB), polyvinylpyrrolidone (PVP), crosslinked acrylic resins, polyurethane, epoxy resins, modified polyolefins, silicon alkoxides, zirconium compounds, colloidal silica, oxirane ring-containing compounds, cellulose and / or water-soluble resins such as cellulose salts. In particular, compounds that are dispersible or soluble in water are preferably used as binders. The binders may be one of the above-mentioned examples used alone or two or more of them may be used in combination.
[0051] The film of the present invention preferably contains inorganic particles. The inorganic particles are preferably contained in layer (I), but may be contained in a layer other than layer (I). By containing inorganic particles, the heat resistance and mechanical properties of the film are improved, short circuits due to thermal shrinkage and foreign matter contamination can be suppressed, and safety can be improved when used as a separator for batteries, etc.
[0052] Specific examples of inorganic particles used in the film of the present invention include inorganic oxide particles such as aluminum oxide, boehmite, silica, titanium oxide, zirconium oxide, iron oxide, and magnesium oxide; inorganic nitride particles such as aluminum nitride and silicon nitride; and poorly soluble ionic crystal particles such as calcium fluoride, barium fluoride, and barium sulfate. Among inorganic particles, aluminum oxide, which is effective in increasing strength, and boehmite or barium sulfate, which is effective in reducing wear of parts in the dispersion process of organic resin particles and inorganic particles, are particularly preferred. Furthermore, these inorganic particles may be used alone or in combination of two or more types. The shape of the inorganic particles used may be spherical, plate-like, needle-like, rod-like, elliptical, or the like, and any shape may be used. Among them, spherical is preferred from the viewpoints of surface modification, dispersibility, and coatability.
[0053] When inorganic particles are contained in layer (I) constituting the film of the present invention, the concentration thereof is preferably 10 to 500 parts by mass, more preferably 10 to 250 parts by mass, per 100 parts by mass of the organic particles, from the viewpoint of improving heat resistance.
[0054] The film of the present invention preferably has a non-porous layer and a porous layer after heat treatment at 120°C for 10 minutes. By having the above structure, excellent safety can be achieved when the film is used as a separator for a secondary battery. The non-porous layer is formed when the organic particles remain on the surface layer of the substrate after melting, or when the resin components of the melted organic particles penetrate into a part of the substrate surface to form a mixed layer of layer (I) and the substrate, but do not penetrate completely and remain on the surface layer. This non-porous layer exhibits high insulation properties and can exhibit excellent shutdown properties.
[0055] The film of the present invention preferably has an air resistance at 25° C. of 20 s / 100 ml to 1000 s / 100 ml, and more preferably 20 s / 100 ml to 500 s / 100 ml from the viewpoint of maintaining battery characteristics.
[0056] The film of the present invention has an air resistance of 8.0×10 4 s / 100ml or more is preferable, and 9.0×10 4 s / 100 ml or more is preferable from the viewpoint of improving the shut-down property of the film. The air resistance can be evaluated by the method described later.
[0057] The air resistance of the film of the present invention is preferably 1.7 times or less, and more preferably 1.5 times or less, the air resistance of the porous substrate used in the film at 25° C. If the air resistance of the film having layer (I) and / or layer (II) formed thereon at 25° C. is higher than that of the porous substrate, the practicality of the battery formed therefrom may be poor.
[0058] The puncture strength of the film of the present invention, calculated based on a film thickness of 10 μm, is preferably 5.0 N / 10 μm or more, more preferably 5.5 N / 10 μm or more. The higher the upper limit of the puncture strength, the better, but the physically achievable range is 8.0 N / 10 μm or less. When the puncture strength of the film is within the above range, the short circuit suppression effect when foreign matter is mixed into the battery is enhanced, and safety can be improved. The puncture strength can be achieved by producing a porous substrate using the above composition and the above stretching method.
[0059] The heat shrinkage of the film of the present invention at 120°C for 1 hour is preferably 15% or less, more preferably 12% or less. By setting the heat shrinkage within this range, the dimensional change is small when the temperature inside the battery rises, short circuiting can be suppressed, and high safety can be obtained. The heat shrinkage of the film can be achieved by applying a porous substrate having the molecular weight described above or by using a layer (II) containing inorganic particles described below in combination.
[0060] The electrical resistance of the film of the present invention measured at 25° C. in the untreated state is 0.100 kΩ / cm 2 Preferably, it is 0.050 kΩ / cm or less. 2The above-mentioned properties make it possible to form layer (I) on the porous substrate without impairing the initial electrical properties, and to exhibit excellent electrical properties when the film is used as a separator for a secondary battery.
[0061] The film of the present invention has an electrical resistance of 0.5 KΩ / cm measured at 25° C. after heat treatment at 120° C. for 10 minutes. 2 More than 100.0KΩ / cm 2 More preferably, it is 1.0KΩ / cm or less. 2 More than 100.0kΩ / cm 2 It is more preferable that the electrical resistance is 0.5 kΩ / cm or less after heat treatment at 120° C. for 10 minutes. 2 If the resistance is less than 100 kΩ / cm, the electrical insulation is low when the film is used in a device such as a battery, and thermal runaway cannot be suppressed, so safety cannot be ensured. The higher the electrical resistance, the better, but the achievable range is 100 kΩ / cm. 2 The upper limit is 1. The electrical resistance value after heat treatment at 120°C for 10 minutes can be set within the above range by using a resin having the above composition as the organic particles. The electrical resistance value after heat treatment at 120°C for 10 minutes can be evaluated by the method described below.
[0062] The film of the present invention may also include a layer (II) having a different composition from the layer (I) in addition to the layer (I). Examples of components constituting the layer (II) include, but are not limited to, a composition containing inorganic particles and a binder, a composition containing organic particles made of a component different from the layer (I), and a composition containing PVDF or an acrylic resin having adhesive properties with an electrode. The inorganic particles and binders can be selected from the types described above. In addition, when the layer (II) is provided, it may be laminated on the surface of the layer (I) or may be provided on the opposite side to the layer (I). It is particularly preferable from the viewpoint of improving heat resistance to provide a configuration in which the layer (I) is provided on one side of the porous substrate and the layer (II) is provided on the opposite side to the surface of the porous substrate having the layer (I).
[0063] When the layer (II) is provided in the film of the present invention, its thickness is preferably from 1 μm to 10 μm, and more preferably from 1 μm to 7 μm, from the viewpoint of miniaturization of the battery.
[0064] One embodiment of the present invention includes a secondary battery such as a lithium ion battery or a storage battery device having a positive electrode, the film of the present invention, and a negative electrode. Here, when the film has only layer (I), it is preferable that layer (I) faces the negative electrode from the viewpoint of durability. When the film has layer (I) and layer (II) having a different composition from layer (I), it is preferable that layer (II) faces the positive electrode side of the battery from the viewpoint of improving the durability of the film in the battery.
[0065] The positive electrode is a positive electrode material consisting of an active material, a binder resin, and a conductive assistant layered on a current collector. Examples of the active material include layered lithium-containing transition metal oxides such as LiCoO2, LiNiO2, and Li(NiCoMn)O2, spinel-type manganese oxides such as LiMn2O4, and iron-based compounds such as LiFePO4. The binder resin may be a resin with high oxidation resistance. Specific examples include fluororesin, acrylic resin, and styrene-butadiene resin. Carbon materials such as carbon black and graphite are used as the conductive assistant. Metal foils are suitable for the current collector, and aluminum foils are often used, but are not limited to this.
[0066] The negative electrode is a negative electrode material consisting of an active material and a binder resin laminated on a current collector. The active material can be any of a variety of materials, including carbon materials such as artificial graphite, natural graphite, hard carbon, and soft carbon; lithium alloy materials such as tin and silicon; metal materials such as Li; and lithium titanate (Li4Ti5O 12 ) and the like. As the binder resin for the negative electrode, fluororesin, acrylic resin, styrene-butadiene resin, etc. are used. As the current collector, a metal foil is suitable, and in particular, copper foil is often used, but it is not limited thereto.
[0067] When the secondary battery is a lithium ion battery, a separator made of a film and an electrolyte are interposed between the positive electrode and the negative electrode. In this case, the electrolyte is a place for moving ions between the positive electrode and the negative electrode in the secondary battery. The electrolyte is a solution of an electrolyte in an organic solvent. Examples of the electrolyte include LiPF6, LiBF4, and LiClO4. LiPF6 is preferably used from the viewpoint of solubility in organic solvents and ionic conductivity. Examples of the organic solvent include ethylene carbonate, propylene carbonate, fluoroethylene carbonate, dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate. Two or more of these organic solvents can be mixed and used.
[0068] The method for producing the organic particles and film of the present invention will be specifically described below. An example will be described in which an olefin porous membrane "SETELA" (registered trademark) (manufactured by Toray Industries, Inc., melting point 135°C, thickness 4 μm, air resistance 160s / 100ml) is used as the porous substrate for the film, but the porous substrate is not limited thereto. As the raw material for the organic particles, chips or resin powder of polyolefin resin having the above-mentioned resin properties, particles that have already been microparticulated, etc. are prepared. When the raw material for the organic particles is chips or resin powder, they are subjected to a granulation process, and from the viewpoint of maintaining the thickness of the layer (I), they are subjected to a process such as pulverization and classification until the volume-based particle diameter obtained by the diffraction method becomes 0.1 to 5 μm, more preferably 0.1 to 3 μm. Examples of methods for producing fine particles of organic particles include, but are not limited to, poor solvent crystallization (a method in which organic particles are dissolved in a soluble organic solvent, then a poor solvent is mixed in to crystallize the particles), melt dispersion (a method in which the raw material of organic particles is associated with a dispersion medium in a molten state, then stirred and cooled to form particles), a method in which organic particles prepared by a dry grinding method (a method in which a resin as a raw material of organic particles is physically ground in a dry state to form particles) are dispersed in a solvent and used, and a wet grinding method (a method in which a resin as a raw material of organic particles is mixed with a solvent and then physically ground to form particles). The particles obtained by these methods are dispersed in an arbitrary solvent to form a dispersion. Examples of solvents used as the dispersion medium for the dispersion of organic particles include, but are not limited to, water or organic solvents such as methanol, ethanol, 2-propanol, acetone, tetrahydrofuran, methyl ethyl ketone, ethyl acetate, N-methylpyrrolidone, dimethylacetamide, dimethylformamide, and dimethylformamide. Among these, in consideration of reducing the environmental load, it is preferable to use water or a mixture of water and alcohol as the dispersion medium. Specific methods for dispersing organic particles in a solvent include, but are not limited to, ball mills, bead mills, sand mills, roll mills, homogenizers, ultrasonic homogenizers, high-pressure homogenizers, ultrasonic devices, paint shakers, etc. Furthermore, the particle forming method may be one of the above methods alone, or a combination of a plurality of methods may be used for stepwise processing. Furthermore, if a commercially available dispersion of the above organic particles is available, it may be used.The solid content of the organic particle dispersion is preferably 5 to 60% by mass, more preferably 10 to 50% by mass, from the viewpoint of maintaining the dispersibility of the organic particles in the dispersion. The solid content refers to the components in the dispersion other than the solvent.
[0069] The coating agent forming the layer (I) contained in the film is prepared by blending the organic particle dispersion prepared by the above method so that the solid content of the organic particles is 5 to 30% by mass, and the binder described above is blended so that the solid content is 0.05 to 5% by mass. When the coating agent is water-based, it is preferable to further blend isopropyl alcohol as a wetting improver in an amount of 5 to 15% by mass when the total composition of the coating agent is 100% by mass, and the remainder is ion-exchanged water in an amount of 100% by mass, and to prepare the coating agent by stirring for 4 hours. If necessary, inorganic particles, film-forming assistants, dispersants, thickeners, stabilizers, defoamers, leveling agents, etc. may be added to the coating agent. At this time, the solid content of the coating agent is preferably 5 to 40% by mass, more preferably 10 to 35% by mass, from the viewpoint of stabilizing the coating and drying properties. From the viewpoint of stabilizing coatability, the solution viscosity of the coating material measured at 25°C / 65%RH using a tuning fork vibration viscometer (SV-100, manufactured by A&D Corporation) is preferably 30 to 150 mPa s, more preferably 30 to 120 mPa s.
[0070] The coating agent prepared as above is applied to the porous substrate by any coating method. Any commonly used method can be used as the method for applying the coating agent. For example, dip coating, gravure coating, slit die coating, knife coating, comma coating, kiss coating, roll coating, bar coating, spray coating, immersion coating, spin coating, screen printing, inkjet printing, pad printing, other types of printing, etc. can be used.
[0071] After the coating agent is applied onto the porous substrate using the above method, it is dried for 1 minute at 40 to 100°C, more preferably 50 to 80°C, in order to suppress shrinkage and deformation of the porous substrate, to form a layer (I) having a thickness of 0.5 to 10 μm, more preferably 0.5 to 7 μm.
[0072] The film of the present invention has excellent safety and can be suitably used in electricity storage devices such as hydrogen batteries, air batteries, fuel cells, and lithium ion secondary batteries, as well as capacitors, electric double layer capacitors, and lithium ion capacitors. Among these, the film of the present invention can be suitably used as a separator for electricity storage devices, particularly lithium ion secondary batteries. Furthermore, a secondary battery using the film of the present invention as a separator for the secondary battery has excellent safety by utilizing its characteristics. EXAMPLES
[0073] (1) Characteristics of organic particles a) Composition When the organic particles were in powder form, infrared spectroscopy was taken as is using an FT-IR (PerkinElmer, Frontier GOLD) with a transmission method at an accumulation count of 128 times to identify the resin type of the sample.When the organic particles were in a dispersion form, 5 ml was dispensed into an aluminum dish, dried on a hot plate heated to 40°C, and the solid content was removed as a sample, and the composition was identified using the same method as above.
[0074] b) Softening start temperature The complex viscosity of the sample in (1)a) was measured from 25°C to 150°C at a heating rate of 10°C / min using a dynamic viscoelasticity measuring device (102M manufactured by Anton Paar) under the following measurement conditions, and the temperature at which the complex viscosity started to decrease was read as the softening onset point from the obtained temperature dispersion curve. The measurement was performed with n=3, and the average of the measured values was regarded as the softening onset temperature of the sample. Plate used: φ11.98mm Gap: 1mm Sweep speed 10℃ / min Distortion 1%.
[0075] c) Complex viscosity The complex viscosity of the sample in (1)a) was measured using the same apparatus and conditions as in (1)b), and the complex viscosity (Pa s) at 80°C and 120°C was read from the temperature dispersion curve obtained. Measurements were performed with n=3, and the average values of the measured values were taken as the complex viscosity of the sample at 80°C and 120°C.
[0076] d) Particle size (D50, D10, D90) Prepare a powder of organic particles. Mix the particles with purified water and adjust the dispersion to have a transmittance of around 90%. Then, use a laser light diffraction scattering particle size distribution measuring device (Microtrac MT3000, Nikkiso Co., Ltd.) to measure the particle size distribution of the sample in accordance with JIS Z8825-1:2001 after ultrasonic treatment for 4 minutes at a laser light wavelength of 780 nm and a measurement temperature of 25°C. From the particle size distribution of the sample, determine the particle sizes at 10%, 50%, and 90% of the cumulative distribution (D10, D50, D90).
[0077] e) Maximum absorption peak intensity ratio (S1 / S2) After obtaining the IR spectrum of the organic particles using the same method as in a), the IR spectrum was analyzed using the analysis software spectrum (PerkinElmer). -1 From 1500cm -1 and 1700 cm -1 From 1800cm -1 The maximum absorption peak intensities (S1 and S2) in each range were calculated, and the maximum absorption peak intensity ratio (S1 / S2) was calculated.
[0078] When extracting the organic particles from the film, the organic particles were collected using the method described below in (2) b)-i, and then analyzed in the same manner as above.
[0079] f) Adhesiveness A high-density polyethylene (PE) film TPES-4520 (TRUSCO Co., Ltd., thickness 10 μm) is prepared. 20% by mass of organic particles, 0.15% by mass of carboxymethylcellulose (Daicel Miraizu Co., Ltd., high molecular weight type), 9% by mass of isopropyl alcohol, and 70.8% by mass of ion-exchanged water are mixed as solid contents, stirred for 1 hour to make a coating, which is applied to one side of a PE film, and then dried at 50°C for 1 minute in a hot air oven to form an adhesive layer with a thickness of 1.5 μm. The PE film with the adhesive layer formed on one side is sampled to a size of 30 mm wide x 50 mm long. In addition, an uncoated PE film is cut to the same size, and the coated adhesive layer is overlapped so that it is in the center to make a sample. The surface temperature of the seal bar of a hand sealer (Tamaki Co., Ltd., HY-3) is set to 120°C, and only the tip of the sample, 30 mm wide x 15 mm long, is heat-sealed for 15 seconds. The unlaminated portion of the heat-sealed sample was clamped between the chucks of a universal testing machine (Orientec, AMF / RTA-100, Instron type) and subjected to a 180° peel evaluation at 25° C. with a chuck distance of 10 mm and a pulling speed of 20 mm / min. The evaluation was performed with n=5, and the average value was evaluated according to the following criteria.
[0080] A: Peel strength is 4N / mm or more B: Peel strength is 2N / mm or more and less than 4N / mm C: Peel strength is less than 2N / mm.
[0081] g) Disadvantages A 150 mm x 150 mm piece was cut out from the sample coated with the organic particles prepared in f) at any desired location, and the surface was visually observed to count the number of defects due to surface unevenness and evaluate it according to the following criteria. A: No flaws B: 1 to 4 defects C: 5 or more defects.
[0082] h) Handling To evaluate the handling properties of the unheated film, the sample coated with organic particles prepared in f) and the uncoated PE film were each cut to a size of 30 mm x 50 mm and stacked with the coated side in the center. The stacked samples were pressurized at 25°C and 0.5 MPa for 3 minutes, after which the ability to peel them off by hand was measured and evaluated according to the following criteria.
[0083] A: Cannot be peeled off (films stick strongly to each other when not heated) B: Peelable (films do not stick to each other when not heated).
[0084] (2) Film characteristics a) Constituent layers of the film and thickness of each layer The film is cut into pieces of 5 mm × 5 mm in any direction and fixed on a specimen stage for a scanning electron microscope. This sample is then heated at a vacuum of 100°C using a sputtering device. -3 The cross section was cut by ion etching for 10 minutes under conditions of Torr, voltage 0.25KV, and current 12.5mA, and then the surface was gold sputtered using the same device and observed at a magnification of 3,000 times using a scanning electron microscope (JEOL Ltd., JSM6700F type) to confirm the layer structure of the film. The cross section was identified as containing organic particles and the composition of each layer was analyzed using energy dispersive X-ray analysis (EDX). The thickness of the porous substrate and each layer laminated on the substrate was measured by image processing. A total of 10 samples were selected at random locations, and the average of the measured values of the 10 samples was used as the porous substrate thickness of the sample and the thickness of each layer constituting the porous film.
[0085] b) Composition analysis of organic particles and other constituents / porous substrates i. Components such as organic particles The film cut to A4 size is immersed in 100 ml of water and placed in an ultrasonic cleaner for about 1 hour to extract the coating layer laminated on the surface of the porous substrate. This operation is repeated five times with a new sample to collect about 500 ml of extract. This extract is concentrated to 20 ml while heating to 40 ° C. 30 ml of isopropyl alcohol is added to this concentrated liquid and stirred, and then it is processed at 5000 rpm for 15 minutes using a centrifuge (Koki Holding Co., Ltd., CR21GIII) to separate the components that make up the coating layer based on the difference in specific gravity. Each component separated based on the difference in specific gravity is collected using a micropipette and then dried. After fixing each dried sample to a sample stage for a scanning electron microscope, EDX analysis is performed in the same manner as in a) to perform composition analysis of each component. For samples mainly composed of carbon, infrared spectroscopy spectra are then collected using a FT-IR (PerkinElmer, Frontier GOLD) with a transmission method and an accumulation number of 128 times, and the resin type of the sample is identified.
[0086] ii. Porous base material The water remaining on the surface of the porous substrate after cleaning in i. was wiped off, and an infrared spectrum of the surface of the porous substrate was collected using an FT-IR (PerkinElmer, Frontier GOLD) with an ATR method at an accumulation count of 128 times to identify the resin type. If it was found in (1) a) that the porous substrate was formed of multiple layers, the surface layer was scraped off with a microplane within the range not exceeding the thickness measured in the same evaluation, and each layer was exposed, and the resin type was identified using the same method as above.
[0087] c) Heat treatment at 120℃ for 10 minutes Prepare a SUS metal frame with outer dimensions of 140mm x 140mm, inner dimensions of 100mm x 100mm, and thickness of 2mm. Attach Nitto Denko double-sided tape (No. 501F) to all four sides of the metal frame, attach the film to the metal frame without slack, and then heat it in a hot air oven for 10 minutes after the temperature is raised to 120°C. After the film is heated, it is removed from the hot air oven and cooled, and then cut out along the inner dimensions of the metal frame to obtain a sample.
[0088] d) Air permeability resistance A sample of 100 mm × 100 mm was cut out from any part of the untreated film, and the air resistance (s / 100 ml) was evaluated in an environment of 25° C. (n=5). In addition, the sample heat-treated at 120° C. obtained in (2) c) was also evaluated in an environment of 25° C. (n=5), and the air resistance (s / 100 ml) of the sample after heat treatment at 120° C. was obtained.
[0089] e) Film puncture strength (N / 10μm) The puncture strength was measured in accordance with JIS Z 1707 (2019), except that the test speed was 2 mm / sec. Using a force gauge (IMADA Co., Ltd. DS2-20N), the puncture strength (N) of the film was measured in an atmosphere of 25°C with a needle of 1.0 mm diameter and a spherical tip (radius of curvature R: 0.5 mm), and the puncture strength (N / 10 μm) of the film converted to a film thickness of 10 μm was calculated using the following formula.
[0090] Puncture strength of film (N / 10 μm) = puncture strength / film thickness (μm) × 10 (μm).
[0091] f) Heat shrinkage rate (%) at 120℃ / 1 hour A square sample of 5 cm x 5 cm was cut out in any direction of the film. The length of one side of the cut out sample and the other piece perpendicular to it were measured, and the average of the lengths in the two directions was calculated and defined as the untreated sample length L(b) [cm]. Next, the sample was placed in an oven with an internal temperature of 120°C and heated. After one hour from the placement, it was taken out and the lengths of the sides in the two directions were measured and the average was calculated as the sample length L(a) [cm] after heating. L(a) and L(b) were inserted into the following formula to calculate the thermal shrinkage rate when heat-treated at 120°C for one hour. This measurement was also performed at three arbitrary points on the sample surface, and the average value was defined as the thermal shrinkage rate (%) after 1 hour at 120°C.
[0092] Heat shrinkage rate (%) = 100 × (L(b) - L(a)) / L(b).
[0093] g) Shutdown property (electrical resistance) The untreated film and the sample heat-treated at 120°C obtained in (2) c) were punched out from any point into a disk-shaped sample with a diameter of 22 mm, immersed in the electrolyte for 24 hours, and then removed to prepare a sample. A 0.1 mm thick SUS plate was punched out into a 16 mm circle. The SUS plate / separator / SUS plate were stacked in this order in a nitrogen-substituted glove box and stored in an HS cell (manufactured by Hosen Co., Ltd.), electrolyte was injected, and the cell was tightened and sealed with screws. The electrolyte used was a solvent made of a 1:1 volumetric mixture of EC (ethylene carbonate) and DEC (diethyl carbonate), in which 1 mol / L of LiB6 was dissolved as a solute. The terminals of this cell were connected to an impedance measurement system (manufactured by Princeton Applied Research, product name "VersaSTAT-4"), and AC impedance (kΩ) was measured by applying a voltage with a voltage amplitude of 10 mV and a frequency of 1 MHz to 10 kHz. The real part of the obtained AC impedance was plotted on the X-axis and the imaginary part on the Y-axis to obtain a Cole-Cole plot. The value of the real part (kΩ) at the intersection of this plot with the X-axis was calculated based on the area (cm2) of the SUS plate used. 2 ) to obtain the electrical resistance (kΩ / cm 2 The evaluation was performed with n=5, and the average value was used to evaluate the electrical resistance of the sample according to the following criteria.
[0094] [Unprocessed] A: 0.050kΩ / cm 2 less than B: 0.050kΩ / cm 2 More than 0.100kΩ / cm 2 less than C: 0.100kΩ / cm 2 End [After heat treatment at 120℃] A: 1.0KΩ / cm 2 End B: 0.7KΩ / cm 2 More than 1.0kΩ / cm 2 less than C: 0.7KΩ / cm 2less than.
[0095] h) Short Circuit The short circuit resistance when the film was used as a separator was evaluated using a tabletop precision universal testing machine Autograph AGS-X (Shimadzu Corporation). A sample laminate was made by laminating the following in order: polypropylene insulator (thickness 0.2 μm) / negative electrode (for lithium ion batteries (copper foil (thickness approximately 0.9 μm), active material: artificial graphite (particle size approximately 13 μm)) / separator / 500 μm diameter chrome ball (material: chrome (SUJ-2)) / aluminum foil. The aluminum foil and negative electrode of the sample laminate were connected by a cable to a circuit consisting of a capacitor and a clad resistor. The capacitor was charged to approximately 1.5 V, and a metal ball (material: chrome) with a diameter of approximately 500 μm was inserted between the separator and aluminum foil in the sample laminate. A metal ball (SUJ-2) was placed on the sample laminate. The sample laminate was then pressed at 0.3 mm / min, and foreign matter resistance was evaluated based on the amount of displacement until the battery shorted out. The point at which the leakage current value began to increase during the change in compressive load was taken as the starting point, and the moment a short circuit was formed via the metal ball and current was detected as the short-circuit point, and the amount of displacement at each point was measured. The more the sample did not short out even with a large amount of displacement, the better its foreign matter resistance was, and the relationship between the amount of displacement and foreign matter resistance was divided into two stages as shown below. Stage A is preferable as it leads to higher energy density and capacity of batteries. A: Displacement (mm) / separator thickness (μm) is greater than 0.02. B: Displacement (mm) / separator thickness (μm) is 0.02 or less.
[0096] (Reference example 1) LDPE (Sumitomo Chemical Co., Ltd., Sumikathene (MFR 75g / 10min)) and PE-wax (Mitsui Chemicals, Inc., Hiwax modified type A (acid value 30mgKOH / g) were weighed out in the amounts of A-1 shown in Table 1, then dry-blended, and fed to a vented co-rotating twin-screw kneading extruder (Japan Steel Works, Ltd., screw diameter 30mm, screw length / screw diameter = 45.5) heated to 150°C, melt-extruded and discharged in the form of strands, pelletized with water at 25°C, cooled with water at a temperature of 25°C, and immediately cut to obtain pellets. Next, 1.8 kg of the pellets obtained above and 4.02 kg of water were added to a jacketed pressure-resistant autoclave with an inner diameter of 50 mm, height of 110 mm, and a capacity of 20 L equipped with a turbine-type stirring blade with a diameter of 30 mm. g and 0.18 kg of polyoxyethylene fatty acid amide (ethylene oxide 15 mole adduct) were charged and sealed. The inside of the autoclave was heated to 150°C by circulating heated oil in the jacket, and then the stirrer was started. The inside temperature was kept at 150°C and stirred at 250 rpm for 30 minutes, and then the contents were cooled to 50°C and removed from the autoclave to obtain an aqueous dispersion containing organic particles A-1. 10 ml of this dispersion was dispensed into an aluminum dish and dried on a hot plate heated to 40°C, and the solid content was removed to obtain a powder of organic particles A-1. Using this organic particles A-1, various particle properties were evaluated.
[0097] Example 1 The dispersion containing the organic particles A-1 described in Reference Example 1 was concentrated to a solid content concentration of 25% by mass, and 15 g of this emulsion was mixed with 0.02 g of carboxymethylcellulose (manufactured by Daicel Miraizu Co., Ltd., high molecular weight type), 1.8 g of isopropyl alcohol, and 3.16 g of ion-exchanged water, and the mixture was stirred for 1 hour to prepare a coating agent. A high-density polyethylene (PE) film TPES-4520 (TRUSCO Co., Ltd., thickness 10 μm) was prepared as a substrate, and the coating agent was applied to one side using a bar coater, and dried at 50° C. for 1 minute to obtain a film laminated with an adhesive layer having a coating thickness of 1.5 μm.
[0098] (Examples 2 and 3, Comparative Example 2) Aqueous dispersions containing organic particles A-2 to A-4 were obtained in the same manner as in Reference Example 1, except that LDPE (Sumitomo Chemical Co., Ltd., Sumikathene (MFR 75 g / 10 min)) and PE-wax (Mitsui Chemicals, Inc., Hiwax modified type A (acid value 30 mgKOH / g)) were weighed out in the amounts shown in Table 1. The dispersions were concentrated to a solid content concentration of 25 mass%, and then the same coating composition as in Example 1 was prepared. Coating was performed under the same conditions to obtain a film laminated with an adhesive layer having a coating thickness of 1.5 μm.
[0099] Example 4 An aqueous dispersion containing organic particles B was obtained in the same manner as in Example 1, except that LDPE (Sumitomo Chemical Co., Ltd., Sumikathene (MFR 75 g / 10 min)) and PE-wax (Mitsui Chemicals, Inc., Hiwax modified type B (acid value 60 mg KOH / g)) were weighed out in the amounts shown in Table 1 and then dry-blended. This dispersion was concentrated to a solid content concentration of 25 mass%, and then the same coating composition as in Example 1 was prepared and coated under the same conditions to obtain a film laminated with an adhesive layer having a coating thickness of 1.5 μm.
[0100] Example 5 An aqueous dispersion containing organic particles C was obtained in the same manner as in Example 1, except that LDPE (Sumitomo Chemical Co., Ltd., Sumikathene (MFR 75 g / 10 min)) and PE-wax (Mitsui Chemicals, Inc., Hiwax modified type C (acid value 15 mgKOH / g)) were weighed out in the amounts shown in Table 1 and then dry-blended. This dispersion was concentrated to a solid content concentration of 25 mass%, and then the same coating composition as in Example 1 was prepared and coated under the same conditions to obtain a film laminated with an adhesive layer having a coating thickness of 1.5 μm.
[0101] Example 6 An aqueous dispersion containing organic particles D was obtained in the same manner as in Example 1, except that PE-wax (UNISID (acid value 120 mgKOH / g) manufactured by NuCera Solution) was weighed out in the amount shown in Table 1 and then dry-blended. This dispersion was concentrated to a solid content concentration of 25 mass%, and then the same coating composition as in Example 1 was prepared and coated under the same conditions to obtain a film laminated with an adhesive layer having a coating thickness of 1.5 μm.
[0102] Comparative Example 1 An aqueous dispersion containing organic particles E was obtained in the same manner as in Example 1, except that PE-wax (manufactured by Mitsui Chemicals, Inc., Hiwax unmodified type) was used alone. This dispersion was concentrated to a solid content concentration of 25 mass%, and then the same coating composition as in Example 1 was prepared and coated under the same conditions to obtain a film laminated with an adhesive layer having a coating thickness of 1.5 μm.
[0103] Comparative Example 3 An aqueous dispersion containing organic particles F was obtained in the same manner as in Example 1, except that PE-wax (manufactured by Mitsui Chemicals, Inc., Hiwax modified type A (acid value 30 mgKOH / g) was used alone as the resin component. This dispersion was concentrated to a solid content concentration of 25 mass%, and then the same coating composition as in Example 1 was prepared and coated under the same conditions to obtain a film laminated with an adhesive layer having a coating thickness of 1.5 μm.
[0104] Comparative Example 4 An aqueous dispersion containing organic particles G was obtained in the same manner as in Example 1, except that copolymerized PE (Arkema, Rotader (MFR 75 g / 10 min) was used alone as the resin component. This dispersion was concentrated to a solid content concentration of 25 mass%, and then the same coating composition as in Example 1 was prepared and coated under the same conditions to obtain a film laminated with an adhesive layer having a coating thickness of 1.5 μm.
[0105] (Examples 7 to 12, Comparative Examples 5 to 8) A polyolefin microporous membrane "SETELA" (registered trademark) (manufactured by Toray Industries, Inc., raw material: polyethylene, melting point 135°C, thickness 4 μm, air resistance 160 s / 100 ml) was used as a porous substrate, and a coating agent containing an aqueous dispersion containing various organic particles prepared in Examples 1 to 6 and Comparative Examples 1 to 4 was applied to the porous substrate using a bar coater and dried at 50°C for 1 minute to obtain a film having a layer (I) containing organic particles with a coating thickness of 1.5 μm laminated on one side.
[0106] (Example 13) 7.5g of an aqueous dispersion of organic particles A-2 with a solid content concentration of 25% by mass, 0.02g of carboxymethylcellulose (manufactured by Daicel Miraize Co., Ltd., high molecular weight type), 1.8g of isopropyl alcohol, 7.5g of alumina (manufactured by Nippon Light Metal Co., Ltd., average particle size 0.5 μm) as inorganic particles, 0.009g of a leveling agent (manufactured by 3M Co., Ltd., fluorine-containing type), and 3.16g of ion-exchanged water were mixed and stirred for 1 hour to obtain a coating agent. A polyolefin microporous film "SETELA" (registered trademark) (manufactured by Toray Industries, Inc., raw material: polyethylene, melting point 135 ° C., thickness 4 μm, air resistance 160s / 100 ml) was used as a porous substrate, and the coating agent prepared on the porous substrate was applied using a bar coater and dried at 50 ° C. for 1 minute to obtain a film in which a layer (I) containing organic particles and inorganic particles made of A-2 with a coating thickness of 3 μm was laminated on one side.
[0107] Example 14 A film was prepared in which a layer (I) containing organic particles A-2 was laminated to a thickness of 1.5 μm on one side in the same manner as in Example 8. Next, a coating agent was prepared by mixing 0.05% by mass of a leveling agent (manufactured by 3M, fluorine-containing type), 0.2% by mass of carboxymethylcellulose (manufactured by Daicel Miraizu Co., Ltd., high molecular weight type), 20% by mass of alumina (manufactured by Nippon Light Metal Co., Ltd., average particle size 0.5 μm) as inorganic particles, 10% by mass of isopropyl alcohol, and 69.75% by mass of ion-exchanged water on the other side, and then coated using a bar coater, and dried at 50 ° C. for 1 minute to form a layer (II), and a film was obtained in which a layer (I) containing organic particles made of A-2 with a coating thickness of 1.5 μm was laminated on one side, and a layer (II) made of inorganic particles with a coating thickness of 1.5 μm was laminated on the other side.
[0108] Example 15 Mw is 15×10 5 80 parts by mass of liquid paraffin was added to 20 parts by mass of ultra-high molecular weight polyethylene, and 0.4 parts by mass of 2,6-di-t-butyl-p-cresol and 0.7 parts by mass of tetrakis[methylene-3-(3,5-di-t-butyl-4-hydroxyphenyl)-propionate]methane were added as antioxidants and mixed to prepare a polyethylene resin solution. The obtained polyethylene resin solution was charged into a twin-screw extruder and kneaded at 180°C to prepare a polyethylene solution. The obtained polyethylene solution was fed into a T-die, and the extrudate was cooled with a cooling roll controlled at 35°C to form a gel-like sheet. The obtained gel-like sheet was subjected to simultaneous biaxial stretching at a stretching temperature of 105°C to 5x5 times using a tenter system. The stretched film was washed in a washing tank of methylene chloride to remove the liquid paraffin. The washed membrane is dried, and then re-longitudinally stretched by 1.6 times at 100℃ by roll stretching method, and then re-transversely stretched by 1.5 times at 139℃ by tenter method, to obtain a polyolefin microporous membrane of ultra-high molecular weight polyethylene with a thickness of 4μm and an air resistance of 160s / 100ml.This polyolefin microporous membrane is used as a porous substrate, and the film obtained is laminated on one side of the porous substrate with the layer (I) containing particles of A-2 with a coating thickness of 1.5μm in the same manner as in Example 8.
[0109] Table 1 shows the details of the raw materials and compounding ratios of the organic particles used in Examples 1 to 15 and Comparative Examples 1 to 8.
[0110] Tables 2 and 3 show the types of organic particles used in the films prepared in Examples 1 to 15 and Comparative Examples 1 to 8, and the evaluation results of the prepared films.
[0111] [Table 1]
[0112] [Table 2]
[0113]
Table 3
Claims
1. The main component is polyolefin, and the FT-IR spectrum shows a peak at 1400 cm -1 More than 1500cm -1 The maximum absorption peak intensity (S 1 ) 1700cm -1 More than 1800cm -1 The maximum absorption peak intensity (S 2 ) to the ratio (S 1 / S 2 ) is 2 or more and 100 or less.
2. Complex viscosity at 120°C is 1.0 x 10 2 Pa・s or more 5.0×10 3 The organic particles according to claim 1, having a viscosity of not more than Pa·s.
3. In the FT-IR spectrum, 1400 cm -1 More than 1500cm -1 The maximum absorption peak intensity (S 1 ) 1700cm -1 More than 1800cm -1 The maximum absorption peak intensity (S 2 ) to the ratio (S 1 / S 2 3. The organic particle according to claim 1, wherein the molecular weight is 5 or more and 75 or less.
4. The organic particles according to claim 1 or 2, having a D50 of 0.05 μm or more and 1.5 μm or less.
5. The organic particles according to claim 1 or 2, having a D90 of 2.0 μm or less.
6. The organic particles according to claim 1 or 2, wherein D10 is 0.02 μm or more.
7. A dispersion in which the organic particles according to claim 1 are dispersed in water and / or an organic solvent.
8. A film comprising the organic particles according to claim 1.
9. An electricity storage device comprising the organic particles according to claim 1.
10. A film having a layer (I) containing organic particles on at least one surface of a porous substrate, the organic particles being mainly composed of polyolefin, and having a wavelength of 1400 cm in FT-IR spectrum. -1 More than 1500cm -1 The maximum absorption peak intensity (S 1 ) 1700cm -1 More than 1800cm -1 The maximum absorption peak intensity (S 2 ) to the ratio (S 1 / S 2 ) is 2 or more and 100 or less.
11. The complex viscosity of the organic particles at 120° C. is 1.0×10 2 Pa・s or more 5.0×10 3 The film of claim 10 having a viscosity of less than or equal to Pa·s.
12. In the FT-IR spectrum of the organic particles, -1 More than 1500cm -1 The maximum absorption peak intensity (S 1 ) 1700cm -1 More than 1800cm -1 The maximum absorption peak intensity (S 2 ) to the ratio (S 1 / S 2 12. The film according to claim 10 or 11, wherein the value of the linear modulus is 5 or more and 75 or less.
13. 12. The film of claim 10 or 11, wherein the layer (I) comprises inorganic particles.
14. The film according to claim 10 or 11, wherein the porous substrate is based on polyolefin.
15. The film according to claim 10 or 11, having a 10 μm converted puncture strength of 5.0 N / μm or more.
16. The film according to claim 10 or 11, which has a layer (II) having a composition different from that of layer (I) on the other surface of the porous substrate.
17. 17. An electricity storage device having a positive electrode, the film according to claim 16, and a negative electrode, wherein the layer (I) of the film is disposed facing the negative electrode side and the layer (II) is disposed facing the positive electrode side.
18. An electricity storage device comprising the film according to claim 8 or 10.
Citation Information
Patent Citations
JP1803328B
Extrusion molding of plastic form
JP1981056844A
Manual stop mechanism of tape recorder
JP1982078657A
Modified fine polyethylene particle dispersion and production thereof
JP1989045448A
Diaphragm for battery and its manufacture
JP1997219185A